Development of an Antimony Doped Tin Oxide/TiO2 Double-Layers Coated HGM: A High Reflectivity and Low Transmittance Building Thermal Conservation Material. (May 2017) - Yan, Hu; Hong, Zhong; Yuanhao, Wang; Hongxing, Yang
Abstract: A novel antimony doped tin oxide (ATO) and TiO2 double-layers coated HGM was developed in this project. The ATO, which has excellent IR-insulation property, was coated on the HGM as the first layer and the TiO2, which has high reflectivity, was the outmost layer. Therefore, when the modified HGM is coated on the outside of the building walls, the incident light is firstly reflected by the TiO2 layer then insulated by the ATO layer. Most of the radiative thermal transfer was blocked by this double-layers coating. The building envelope can be thus protected by the HGM for less heat gains. Compared with original HGMs, the reflectivity increased by 19.6% and the transmittance decreased by 85.7%. In addition, this coating barely changed the thermal conductivity, which only increased by about 8%. By this method, most of the thermal conduction and radiative thermal transfer are blocked. The energy consumption and carbon emission of a building can be reduced.